Sosialisasi UMKM Pembuatan Permen Daun Kelor di Desa Mekar Sari - Tia Melati; Ahmad Fauzan Pulungan; Fauziah Nasution; Habibina Menatri (Masyarakat Ekonomi Syariah Bogor, 2024)
Community Service Program (KKN) is a platform for applying and developing knowledge and technology outside the campus, with a specific timeframe, work mechanism, and set requirements. KKN organized by Higher Education Institutions aims to enhance the quality of education for students, allowing them to gain greater added value in higher education. Through the implementation of KKN, it is expected that students can develop their social and personal competencies. This KKN program took place from July 25 to August 24, 2024, in Mekar Sari Village, Laut Tador Subdistrict, Batubara Regency. Mekar Sari Village is rich in natural resources that need to be developed to improve the welfare of the community. One of the programs initiated in this KKN is the socialization of making candy from moringa leaves as a Micro, Small, and Medium Enterprises (UMKM) product. This program aims to add value to existing natural resources while empowering the village community by improving their skills and income. By utilizing local potential, it is hoped that Mekar Sari Village can develop a sustainable home industry and have a positive impact on the village's economy. This socialization program includes technical training in candy production, product packaging, and effective marketing strategies to ensure the product can compete in wider markets.